Institutional and Community Collaboration to Support New Approaches to Digital Archiving: A case study of the University of Saskatchewan Library and PAVED Arts artist-run centre - Lucky, Shannon (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2019)
Collaborations between traditional knowledge institutions and communities can have a significant impact on both partners when we look to the strengths each bring to a project rather than asking community partners to fit into established ways of working. This paper discusses my partnership as a researcher at the University of Saskatchewan Library and PAVED Arts artist-run centre leadership and how this project challenges the authority and utility of library standards. We propose a collaborative model that matches the infrastructure and technical expertise of the library with the contextual and historical knowledge PAVED has of their unique and locally important collection.